E-Government-Based Village Fund Allocation Management: Study of Siskeudes in Padakkalawa Village, Pinrang Regency - Eka Susanti; Abdi Abdi; Rudi Hardi (Mengeja Indonesia Publisher, 2021)
Information and communication technology development has produced a public service model through E-government. The government issued a policy, namely the formation of Village Fund Allocations (ADD), to manifest financial decentralization towards independent villages. The village has a very strategic role as a government organizational unit that deals directly with the community with all backgrounds, interests, and needs. The purpose of writing this thesis is to find out the E-government-Based Village Fund Allocation Management System in the Village Finance Application (Siskeudes) in Padakkalawa Village, Pinrang Regency. This study used descriptive qualitative research. Data collection techniques are carried out by direct observation, interviews, and documentation. The theory used in this study is the theory of Arifiyanto and Kurrohman based on four indicators, including planning, implementation, supervision, and reporting/responsibility. The results showed the E-government-Based Village Fund Allocation Management (Study Siskeudes in Padakkalawa Village, Pinrang Regency). In the planning process, Siskeudes obtain data information about the Village Strategic Plan, village RPJM and establish a village development work plan (RKPDes). At the implementation stage, Siskeudes is used for the APBDesa preparation process. For the supervision stage, Siskeudes is used to provide information to supervisors. Moreover, the Siskeudes accountability reporting stage is used to apply the principle of transparency or information disclosed to the public with evidence of the implementation of financial reporting displayed through information boards or accessed through the website.